2014
DOI: 10.1038/nm.3459
|View full text |Cite
|
Sign up to set email alerts
|

An abundant dysfunctional apolipoprotein A1 in human atheroma

Abstract: Recent studies indicate high density lipoproteins (HDL) and their major structural protein, apolipoprotein A1 (apoA1), recovered from human atheroma, are dysfunctional and extensively oxidized by myeloperoxidase (MPO), while in vitro oxidation of apoA1/HDL by MPO impairs its cholesterol acceptor function. We developed a high affinity monoclonal antibody (mAb) that specifically recognizes apoA1/HDL modified by the MPO/H2O2/Cl-system using phage display affinity maturation. An oxindolyl alanine (2-OH-Trp) moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
322
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(339 citation statements)
references
References 66 publications
13
322
0
4
Order By: Relevance
“…135 Also, apoA-I with oxidative modification of the tryptophan residue Trp-72, a form of apoA-I that is highly prevalent in apoA-I recovered from atheroma and increased in the plasma of patients with cardiovascular disease or CAD, had significantly lower cholesterol acceptor capacity. 131 Mechanistically, MPO-dependent chlorination of apoA-I interfered with the binding of apoA-I to ABCA1 and as a consequence chlorinated apoA-I failed to activate the accompanying JAK2 signaling. 132 However, it must be noted that in plasma less than 200 of 1 million apoA-I molecules contain oxidized Tyr-192 or Trp-72 residues.…”
Section: Myeloperoxidase-mediated Protein Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…135 Also, apoA-I with oxidative modification of the tryptophan residue Trp-72, a form of apoA-I that is highly prevalent in apoA-I recovered from atheroma and increased in the plasma of patients with cardiovascular disease or CAD, had significantly lower cholesterol acceptor capacity. 131 Mechanistically, MPO-dependent chlorination of apoA-I interfered with the binding of apoA-I to ABCA1 and as a consequence chlorinated apoA-I failed to activate the accompanying JAK2 signaling. 132 However, it must be noted that in plasma less than 200 of 1 million apoA-I molecules contain oxidized Tyr-192 or Trp-72 residues.…”
Section: Myeloperoxidase-mediated Protein Modificationsmentioning
confidence: 99%
“…132 However, it must be noted that in plasma less than 200 of 1 million apoA-I molecules contain oxidized Tyr-192 or Trp-72 residues. 129, 131 In view of their very low quantity it is unlikely that these modifications reduce cholesterol efflux capacity of (apoB-free) plasma or HDL by simple loss-of-function in the interaction with ABCA1. Rather additional gain of dysfunction is necessary to explain reduced ABCA1-mediated cholesterol efflux capacity of plasma by these modifications.…”
Section: Myeloperoxidase-mediated Protein Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 MPO-mediated oxidation of Trp 72 leads to the formation of the oxTrp72-ApoA1 variant that is abundantly present (20% of total apoA1 in atherosclerotic vessels) in the plaque and lack an ability to activate ABCA1. 77 MPO-dependent nitration and chlorination of ApoA1 at Tyr 192 along with methionine oxidation results in a loss of ability to activate RCT. 78,79 Modified ApoA1 form HDL with impaired function.…”
Section: Role Of Modified Apoa1 In Atherosclerosismentioning
confidence: 99%
“…The 2-OH-Trp moiety is the immunogenic epitope recognized by a high-affinity monoclonal antibody that is also capable to bind to HDL treated with MPO. 77 Recently, Teixeira et al 83 found two novel immunoreactive peptides recognizable by self-antibodies from MI patients with higher titers of ApoA1 IgG. The first peptide (peptide C) comprises 28 residues (Gln 240 -Gln 267 ) and includes a whole non-polar α-helix involved in lipid solubilization.…”
Section: Apoa1 Epitopesmentioning
confidence: 99%